Effect of Lumbar Flexion on the Extent of Epidural Blockade. Issue 6 (1st November 2007) - Kim, Jin-Tae; Lee, Jong-Hwan; Yoon, Seung-Zhoo; Lim, Young-Jin; Bahk, Jae-Hyon; Kim, Chong-Sung; Jeon, Yunseok
Abstract : Background and Objectives: This study examined the effect of lumbar flexion on the extent of the epidural block during lumbar epidural anesthesia. Methods: The epidural catheter was introduced at the L3-4 interspace with the patient in the lateral decubitus position with the surgical side down. After administering a test drug (3 mL of 2% lidocaine and 15 μg of epinephrine), the patients were randomly allocated to 1 of 2 groups: Group F (n = 16, lumbar spine flexed) and Group N (n = 17, lumbar spine in the neutral position). In both groups, 2% lidocaine (16 mL) mixed with sodium bicarbonate (2 mL) was administered through the epidural catheter while the patient maintained the lateral decubitus position with the lumbar spine either flexed or in the neutral position. All the patients maintained their respective positions for 5 minutes and were subsequently turned to the supine position. The pinprick block level and the degree of motor blockade were assessed every 10 minutes for 60 minutes after administering the local anesthetics. A 2-dermatomal difference in uppermost block between groups was determined to be clinically significant. Results: The median difference between groups in the uppermost pinprick block level was only 1.5 dermatomes and it did not satisfy our criteria for clinical significance. There were no significant differences between the 2 groups in the lowermost pinprick block level and the degree of motor block. Conclusions: Lumbar flexion has no clinically relevant effect on sensory spread during epidural anesthesia.